Producto turístico sostenible para el desarrollo socioeconómico de la parroquia Honorato Vásquez del cantón Santa Ana - Álvarez Bermúdez, Carmen Adriana (2014)
With the aim of promoting tourism and development socio- economic of communities of Canton Santa Ana development sustainable tourism product in the parish for which Honorato Vásquez was due primarily gather information on the tourism infrastructure of the parish, besides this an inventory of tourism resources in a matrix Honorato Vasquez used to determine the tourism potential of each of these resources was conducted. With the information gathered previously proceeded to market research, first tourism in the parish was determined for this point the available places for tourism in both accommodation and catering were counted. Strengths, weaknesses, opportunities and threats of tourism in the parish mediate EFI and EFE matrices were determined, the jurisdiction of the parish through competitive profile matrix was defined. The study of the potential demand was conducted to determine the target market. Determining the potential of the product attributes accommodation, catering, transport, service and resource guidance was established. The tourism product structuring three itineraries covering the various resources of the parish and the sale price was determined for each itinerary is designed. The economic viability of developing the product balance point was found, revealing that in the 3 itineraries profitability will sell from 10 packs, and this confirms that the research will contribute to the development of tourism in the communities of Canton Santa Ana.